2020
DOI: 10.1097/sle.0000000000000834
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Weight Loss Outcomes in Laparoscopic Vertical Sleeve Gastrectomy (LVSG) Versus Laparoscopic Roux-en-Y Gastric Bypass (LRYGB) Procedures: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Laparoscopic vertical sleeve gastrectomy (LVSG) has overtaken the laparoscopic Roux-en-Y gastric bypass (LRYGB) as the most frequently performed bariatric surgical procedure. To date little has been reported on the long-term outcomes of the LVSG procedure comparative to the traditionally favoured LRYGB. We undertook a systematic review and meta-analysis to review the five year outcomes of comparing LVSG and LRYGB.We undertook a systematic review and meta-analysis to compare five year weight loss ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…In conclusion the results and conclusions presented in our published paper [2] remain largely unchanged by our reanalysis omitting of the Ruiz-Tovar et al study. Its absence, however, adds to the limitations outlined in our paper and further highlights the critical need for more long-term studies comparing these two procedures.…”
Section: Percent Excess Bmi Loss Data (%Ebmil)supporting
confidence: 52%
See 1 more Smart Citation
“…In conclusion the results and conclusions presented in our published paper [2] remain largely unchanged by our reanalysis omitting of the Ruiz-Tovar et al study. Its absence, however, adds to the limitations outlined in our paper and further highlights the critical need for more long-term studies comparing these two procedures.…”
Section: Percent Excess Bmi Loss Data (%Ebmil)supporting
confidence: 52%
“…We reanalysed all relevant data omitting the Ruiz-Tovar et al study [3], using the methods outlined in our published article [2].…”
mentioning
confidence: 99%
“…Most of the studies demonstrated and maintained weight loss through follow-up at five years and even for longer intervals (up to 11 years) [43]. However, a slow weight gain between the second and third years of postsurgery follow-up is found, increasing up to 5 years postsurgery [45]. Although, based on previous reviews, our results could be generalized to long-term weight loss, we cannot confirm this hypothesis without data.…”
Section: Discussionmentioning
confidence: 56%
“…3 The laparoscopic vertical sleeve gastrectomy (LVSG) is now the most frequently performed bariatric surgical procedure in the United States, having overtaken the laparoscopic Roux-en-Y gastric bypass (LRYGB) which has historically been considered the gold standard for bariatric surgical outcomes. 2 While these procedures are effective at facilitating long-term weight loss, 4 the long-term complication profile of these 2 procedures are still being elucidated, particularly in respect to their relative benefits and risks.…”
mentioning
confidence: 99%
“…This systematic review and meta-analysis has been undertaken to compare the ≥ 5 years late complications reported between LRYGB with LVSG procedures in randomized controlled trials (RCTs): It represents a continuation of our previous works on this topic. [4][5][6]…”
mentioning
confidence: 99%